The Influence of obesity and overweight on the incidence of gastrointestinal tumors - a systematic review of the literature - Grad, Sylwia; Jaremek, Anna; Kępa, Joanna; Kandefer, Norbert; Wyszkowski, Michał; Grabarczyk, Aleksandra; Pawlak, Anna; Gregorek, Małgorzata; Gregorek, Paweł (Journal of Education, Health and Sport, 2023)
Introduction: The percentage of the population struggling with the problem of obesity has been steadily increasing in recent years, both among adults and children. Obesity is a chronic disease resulting from a positive energy balance, which does not tend to disappear spontaneously. The etiology of obesity is multidimensional, it is caused by genetic, environmental and behavioral factors. As a result, excessive amounts of adipose tissue are deposited in the body, which leads to an increased risk of various systemic diseases, including cancers of the digestive system. Aim of the study: This review aims to show the relationship between overweight and obesity and the increased incidence of gastrointestinal cancers. Materials and methods: An analysis of previous works present in the PubMed database was performed, using the following keywords: obesity, overweight, obesity and cancer, cancer. Results: The results of the presented publications show the presence of a positive correlation between overweight and obesity, especially abdominal and the occurrence of gastrointestinal cancers.